Statistische Mechanik: 8.7. bis 13.7.1973 - Rost, Hermann; Waldenfels, Wilhelm von (Tagungsbericht, 1973)
D. B. Abraham, Oxford; W. Beiglböck, Heidelberg; M. Breitenecker, Wien; R. S. Ellis, Evanston; H. Föllmer, Frankfurt; J. Fritz, Budapest; H. O. Georgii, Heidelberg; P. Gräff, Garching; G. Grimmett, Oxford; H. Groeneveld, Utrecht; H. R. Grümm, Wien; Th. E. Harris, Los Angeles; M. Jirina, Athen; M. Keane, Göttingen; A. Martin-Löf, Stockholm; S. Miracle-Solé, Zaragoza; M. Mürmann, Heidelberg; F. Postelnicu, Bukarest; C. J. Preston, Oxford; H. Rost, Heidelberg; F. Spitzer, Ithaca; I. Vincze, Budapest; W. von Waldenfels, Heidelberg; R. Wegmann, München
Keywords: Konferenzschrift